Hepatopulmonary Syndrome in Patients with Liver Cirrhosis: Prevalence, Clinical Significance, Clinical Features, Therapeutic Approaches - A. S. Tsymbal; M. A. Karnaushkina; O. S. Arisheva; N. D. Kislyy; Z. D. Kobalava (SINAPS LLC, 2023)
Hepatopulmonary syndrome is a severe complication of chronic liver diseases, significantly reducing the quality and duration of patient's lives, the pathogenetic manifestation of which is hypoxemia and intrapulmonary vasodilation. The disease is widespread enough: according to some authors, up to 35 % of patients with the terminal stage of liver damage suffer from this syndrome. The main clinical manifestation is progressive dyspnea with possible occurrence of platypnea and orthodexia. Diagnosis is difficult, since the "gold standard" - transthoracic echocardiography with intravenous injection of contrast agent - is an invasive procedure requiring specific equipment, that's why it is poorly used in medical institutions of the Russian Federation. Physical examination is used as an additional method, in which we see dyspnea, cyanosis, spider nevi, digital clubbing, but these manifestations are not highly specific. Therefore, there is an urgent need for minimally invasive, widespread diagnostic methods and clinical markers that can provide early verification of the diagnosis. This review presents data on the prevalence, pathogenesis, clinical presentation, diagnosis and treatment of this syndrome. The aim of this review is to structure the current data and the accumulated experience for an earlier verification of the diagnosis and accordingly, to apply the optimal management tactics for patients with this pathology. Liver transplantation is currently the main effective method of treatment. Patients with hepatopulmonary syndrome who underwent liver transplantation have been proven to have better survival rate.